THE ANALYSIS OF THE FINANCIAL PERFORMANCE OF SHARIA COMMERCIAL BANK IN INDONESIA VIEWED FROM CORPORATE GOVERNANCE AND SHARIA COMPLIANCE - Alfadri, Ferri Alfadri (Fakultas Ekonomi dan Bisnis Islam, 2023)
ANALYSIS OF THE FINANCIAL PERFORMANCE OF SHARIA COMMERCIAL BANK IN INDONESIA VIEWED FROM CORPORATE GOVERNANCE AND SHARIA COMPLIANCE Abstract Purpose: This quantitative study aims to analyze the influence of Corporate Governance (CG) and Sharia Compliance (SC) on the financial performance of Sharia Commercial Banks in Indonesia from 2014 to 2020. The research investigates the impact of these factors, both individually and collectively, on key financial indicators. Design/methodology/approach: The study utilizes panel data analysis with a sample of 49 observations. Data sources include reports from the official websites of the Financial Services Authority and Bank Indonesia. Sharia Compliance is assessed using profit-sharing ratios (PSR), zakat performance ratios (ZPR), and equitable distribution ratios (EDR). Quantitative techniques, specifically panel data analysis, are employed for data processing. Findings: The analysis reveals that the ratios of PSR, ZPR, EDR, and Islamic Corporate Governance (ICG) significantly impact the financial performance of Islamic banks, explaining 76.38% of the variance (RÂ² = 0.762975). However, 23.62% of the financial performance variation is attributed to other variables not included in the study. Research limitations/implications: Limitations include the specific focus on Sharia Commercial Banks in Indonesia, and the study's reliance on self-reported data. The results emphasize the importance of CG and SC but acknowledge the presence of unexplored factors influencing financial performance. Practical implications: The study suggests that improving CG and SC practices can enhance the financial performance of Islamic banks. Sharia Commercial Banks are encouraged to focus on PSR, ZPR, and EDR as indicators of Sharia Compliance to build customer trust and loyalty. Keywords: Corporate Governance, Sharia Compliance, financial performance ANALISIS KINERJA KEUANGAN BANK UMUM SYARIAH DI INDONESIA DILIHAT DARI TATA KELOLA PERUSAHAAN DAN KEPATUHAN SYARIAH Abstrak Tujuan: Penelitian kuantitatif ini bertujuan untuk menganalisis pengaruh Corporate Governance (CG) dan Sharia Compliance (SC) terhadap kinerja keuangan Bank Umum Syariah di Indonesia dari tahun 2014 hingga 2020. Penelitian ini menyelidiki dampak dari faktor-faktor ini, baik secara individu maupun kolektif, pada indikator keuangan utama. Desain / metodologi / pendekatan: Penelitian ini menggunakan analisis data panel dengan sampel 49 pengamatan. Sumber data meliputi laporan dari situs resmi Otoritas Jasa Keuangan dan Bank Indonesia. Kepatuhan Syariah dinilai menggunakan rasio bagi hasil (PSR), rasio kinerja zakat (ZPR), dan rasio distribusi yang adil (EDR). Teknik kuantitatif, khususnya analisis data panel, digunakan untuk pengolahan data. Temuan: Analisis mengungkapkan bahwa rasio PSR, ZPR, EDR, dan Islamic Corporate Governance (ICG) secara signifikan mempengaruhi kinerja keuangan bank syariah, menjelaskan 76,38% varians (RÂ² = 0,762975). Namun, 23,62% dari variasi kinerja keuangan dikaitkan dengan variabel lain yang tidak termasuk dalam penelitian. Keterbatasan / implikasi penelitian: Keterbatasan termasuk fokus khusus pada Bank Umum Syariah di Indonesia, dan ketergantungan penelitian pada data yang dilaporkan sendiri. Hasilnya menekankan pentingnya CG dan SC tetapi mengakui adanya faktor-faktor yang belum dijelajahi yang mempengaruhi kinerja keuangan. Implikasi praktis: Studi ini menunjukkan bahwa meningkatkan praktik CG dan SC dapat meningkatkan kinerja keuangan bank syariah. Bank Umum Syariah didorong untuk fokus pada PSR, ZPR, dan EDR sebagai indikator Kepatuhan Syariah untuk membangun kepercayaan dan loyalitas nasabah. Kata kunci: Tata Kelola Perusahaan, Kepatuhan Syariah, kinerja keuangan